Genetic and morpho-physiological differentiation of sugarcane genotypes under drought stress - de Almeida Silva, Marcelo [UNESP] (2020)
Scarced water supply is the main limiting factor to the good growth and development of sugarcane, and implying the need to obtain germplasm tolerant to drought. The objective of this research was to screen out morpho-physiological traits to recognize tolerant and susceptible sugarcane genotypes. Ten sugarcane genotypes were grown under greenhouse conditions and subjected to water deficiency (-W), 50% of the moisture corresponding to the water holding capacity, at 75 days after planting (DAP) while well-watered (+W) conditions, around 22% soil moisture content (100% of water holding capacity), were maintained as control. Data were recorded at 75 days after the beginning of drought stress. Correlations were made to calculate the genetic distance between the genotypes and later to group them by Tocher's optimization method. The traits that contribute for genetic distance quantification were shoot dry matter (23.41%), chlorophyll content (15.12%), abaxial stomatal density (9.79%) and SPAD index (9.56%). The differentiation between the genotypes through their degree of tolerance to water deficit was evident, and the genotypes more tolerant to water restriction were: CTC2, RB92579, IAC91-5155 and SP89-1115. The genotypes CTC2 and RB92579 maintained higher values for most variables under drought stress along with the lowest reductions between +W and-W. These genotypes were superior due to their better resistance to drought than others. Seven groups were constituted by Tocher's method. In conclusion, the most promising crosses (that may generate descendants with high heterotic potential and better performance under drought stress) observed were SP89-1115 and CTC2, belonging to group II (emphasizing that both sugarcane breeding programs can be considered similar due to same germplas bank and the same cultivar selection methods and objetives), with RB92579 and IAC91-5155 belonging to group VI and IV, respectively.